2021
DOI: 10.1097/md.0000000000025559
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the renin-angiotensin-aldosterone system prevents and cures atrial fibrillation

Abstract: Background: Atrial fibrillation (AF) is a type of arrhythmia that represents a severe health hazard. The current therapies for AF have achieved success in some conditions. However, because the mechanisms underlying the occurrence and development of this disease remain unclear, the current treatment for AF often does not achieve the desired outcomes. Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs), which exert robust effects on specific cardiovascular diseases, are wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Previous studies have reached divergent conclusions about the efficacy of RAS inhibition for the primary prevention of AF. Although some studies have shown a reduction in new-onset events with either ACEI or ARB therapy [17], others have not demonstrated a clear benefit [18]. Furthermore, previous studies have shown that MRAs [19,20], betablockers [21], and statins [22] could significantly reduce the risk of NOAF in patients with HF history.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reached divergent conclusions about the efficacy of RAS inhibition for the primary prevention of AF. Although some studies have shown a reduction in new-onset events with either ACEI or ARB therapy [17], others have not demonstrated a clear benefit [18]. Furthermore, previous studies have shown that MRAs [19,20], betablockers [21], and statins [22] could significantly reduce the risk of NOAF in patients with HF history.…”
Section: Discussionmentioning
confidence: 99%
“…Renin angiotensin system (RAS) is suggested to play a key role in the occurrence and development of AF through structural and electrical remodeling. 61 , 62 In addition, RAS blockade therapy has been shown to reduce the relative risk of recurrent AF by 39%. 63 Angiotensin-converting enzyme (ACE) and angiotensin II (Ang II) are the major components of RAS and there is intracellular RAS in cardiac myocytes.…”
Section: Pathophysiological Pathways Between Ra and Afmentioning
confidence: 99%
“…[28][29][30]124 The major pathophysiological mechanisms of AF include atrial remodeling, autonomic nervous system dysfunction, activation of RAS, endothelial dysfunction, increased EAT thickness, higher adiponectin concentrations and IR. 31,32,53,55,62,68,69,81,84 RA is widely involved in these pathophysiological processes. Controversially, some studies have shown an absence of association between RA and the occurrence of new-onset AF.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…However, the evidence for a benefit of beta-blockers in patients with AF only is limited to ventricular rate control and for prevention of symptomatic AF (3)(4)(5). RAS inhibitors may prevent incident and recurrent episodes of AF in some populations, for example AF recurrence in Asian but not in European or American populations (6,7).…”
Section: Introductionmentioning
confidence: 99%